PENGENALAN PEMASARAN DIGITAL DALAM PEMASARAN PRODUK PERTANIAN DI DESA KABBA KABUPATEN PANGKEP - Fausiah Fausiah; Buyung Romadhoni Romadhoni; ST. Syahriati; Naomi Patiung (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat ITB Nobel Indonesia, 2022)
Buying and selling activities can now be done through the virtual world which is now known as online shopping. Many business people use the internet as a marketing medium to attract consumers and increase business profits. However, what happened to the farmers in the village of Kabba, Pangkep Regency, when the harvest arrived, the farmers had to face the reality of low selling prices and the difficulty of marketing their crops. Therefore, it is important to provide socialization of the introduction of digital marketing to agricultural products. The method used in carrying out this activity is counseling and discussion. This activity adds insight and knowledge to farmers to find solutions to problems faced with agricultural product marketing systems, product handling and packaging, the benefits of online marketing, types of online marketing, and tools used in online marketing (digital marketing).